Проблемы закачки масла в систему смазки перед пуском после длительной стоянки двигателя - Вакуленко, В. В.; Ковалев, М. С.; Крот, С. Г.; Кузьминский, В. А.; Чучмарь, И. Д. (НТУ "ХПИ", 2011)
В статье были проанализированы основные проблемы, возникшие при модификации системы питания маслом двигателя дополнительным стравливающим контуром. Дана оценка эффективности использования данной конструкции.

In article the basic problems the systems which have arisen at updating of giving of oil to the engine are analysed by an additional pitting contour. The estimation of efficiency of use of a similar design is given.
Problems of refuelling oil in system of greasing before start-up after long parking of the engine
Keywords: установка силовая; жидкость; газ; контур стравливающий; жиклер